Activation of the polish coastal tourist reception region using the instrument of a Public-Private Partnership - Szwichtenberg, Aleksander (Turyzm/Tourism, 2009)
Public-Private Partnership (PPP) is a form of cooperation between the public sector and the private in order to carry out projects or services traditionally supplied by the public sector. This mode of investment is most commonly applied to the creation of technological infrastructure projects. According to the author PPP will allow coastal tourist communes (gminas) to speed up the implementation of the communication infrastructure, and the sport and recreational infrastructure which are presently major barriers to the development of the tourist economy. This is further confirmed by examples presented in this work.